0400 Cannabis and National Trends of Sedative-Hypnotic Medication Use in the United States. (12th April 2019) - Kaufmann, Christopher N; Han, Benjamin; Malhotra, Atul; Mojtabai, Ramin; Spira, Adam P; Yourman, Lindsey; Moore, Alison A
Abstract: Introduction: Sedative-hypnotic (SDH) medications are often prescribed for treatment of insomnia despite concerns about their safety. There is anecdotal evidence to suggest cannabis, when medicinally used, may be efficacious for insomnia, although it's unclear whether SDH users are now turning to cannabis for sleep, and if so, whether it is used as a substitute. We examine trends in SDH use from 2005-2014 stratified by cannabis user groups. Methods: Data came from 2005-2014 waves of National Health and Nutrition Examination Survey. Participants self-reported cannabis use (never users, past users, and current users [within past year]) and medications currently using prescribed by a doctor. SDHs included benzodiazepines and other non-benzodiazepine hypnotics. We examined trends using logistic regression in order to model changes in the odds of prescribed SDH use over the entire study period (e.g., 2005-2014), and explored differences across cannabis user groups. Our sample was limited to those age 18 to 59 years as only these ages were queried about cannabis use. Results: Overall, 6.0% of current, 5.8% of past, and 3.1% of never cannabis users reported SDH use ( p <0.001). From 2005-2014 the odds of SDH use increased 84% (95% CI=1.05-3.20), with significant increases for current cannabis users (OR=4.49, 95% CI=1.59-12.71), a modest (albeit nonsignificant) increase for past users (OR=1.75, 95% CI=0.84-3.62), and no changes in never users. Conclusion: Sedative-hypnotic use was high in current and past cannabis users and even increased across these groups in the study period. Results suggest cannabis may not be substituting for use of these medications. More research is needed to identify trends in SDH use after 2014 and in older age cohorts, examine trends based on indication for cannabis use (e.g., medicinally and/or recreationally) and determine the ways in which cannabis use may help or worsen insomnia symptoms. Support (If Any): Dr. Han received support from NIDA (K23DA043651). Dr. Spira received grant support from NIA, and honorarium from Springer Nature Switzerland AG for Guest Editing a Special Issue of Current Sleep Medicine Reports. Dr. Moore received support from NIA (P30AG059299).